Research on the Impact of High - Standard Farmland Construction Policy on Agricultural Green Development - Fan, Hongjian; Xia, Liheng (International Journal of Social Sciences and Public Administration, 2025)
Under the dual pressures of global climate change and population growth, agricultural green development has become a critical path to achieving sustainable agriculture. The High - Standard Farmland Construction Policy has significantly promoted agricultural transformation by enhancing resource utilization efficiency, environmental protection, and economic benefits. However, the policy implementation also faces challenges such as ecological risks and high maintenance costs. Current research mainly focuses on single dimensions, lacking long - term systematic analysis and regional comparisons. Future studies should strengthen interdisciplinary integration, establish long - term monitoring mechanisms, and conduct differentiated impact evaluations to optimize policy design and advance the sustainability of agricultural green development.